Fruit / seed freezing tolerance is dependent on developmental status in relation to provenance: a study of Acer pseudoplatanus across Europe - Daws, Matthew I; Pritchard, Hugh W (MTT, 2008)
The effects of fruit maturity, at the time of natural dispersal, on subsequent desiccation tolerance and sub-zero storage was investigated in three lots of Acer pseudoplatanus (sycamore) collected from northern to southern Europe. Fruits from the native plant distribution range in Italy had significantly higher desiccation tolerance (0.16 g H2O g-1 DW) than those from England (0.30) and Norway (0.50), confirming that the maximum potential desiccation tolerance in sycamore exceeds that of the recalcitrant type. In contrast, the unfrozen water content varied only slightly between seedlots, but systematically reduced with development (0.35 to 0.27 g H2O g-1 DW). Maximum survival (60% fruit germination) of seven days sub-zero temperature storage coincided with drying the Italian fruit lot to c. 0.2 g H2O g-1 DW followed by holding at -20ºC, above the onset temperature for freezing, or at -196ºC (liquid nitrogen). Fruit survival was much lower in the Italian fruits when held at this water content and -70ºC, and in all other combinations of water content, temperature and fruit lot provenance. As the risk of nucleation in partially dried fruits held at -20ºC is high, we recommend sycamore fruits are cryopreserved for long-term conservation (1).
Keywords: Ka; Acer pseudoplatanus; type II seed; differential scanning calorimetry; desiccation tolerance; seed maturity